Improving Air Force Command and Control Through Enhanced Agile Combat Support Planning, Execution, Monitoring, and Control Processes - Tripp, Robert S. (RAND Corporation, 2012)
Many factors contribute to imbalances between needed agile combat support (ACS) resources and those available at any given time to simultaneously meet all requirements for contingency and training operations. This report describes ACS process gaps and recommends implementation strategies to facilitate changes needed to improve Air Force command and control through enhanced ACS planning, execution, monitoring, and control processes.